Frontiers and Ghettos : State Violence in Serbia and Israel - Ron, James (Book collections on Project MUSE., 2003)
James Ron uses controversial comparisons between Serbia and Israel to present a novel theory of state violence. Formerly a research consultant to Human Rights Watch and the International Red Cross, Ron witnessed remarkably different patterns of state coercion.